2019
DOI: 10.1002/adsc.201801670
|View full text |Cite
|
Sign up to set email alerts
|

Iodine‐Catalyzed Oxidative Rearrangement of Amines to α‐Amino Acetals and α‐Amino Aldehydes

Abstract: A protocol for iodine-catalyzed oxidative rearrangement of tertiary and secondary amines has been developed. This metal-free protocol provides an atom-economical, efficient access to synthetically useful a-amino acid derivatives from readily available acyclic and cyclic tertiary or secondary amines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Subsequently, the hydrogen atom at the α‐carbon of substrate 1 a is abstracted by the tert ‐butoxyl radical to form α‐amino radical A . Then, the single‐electron oxidation of radical A by iodine provides iminium ion B , which is deprotonated to afford enamine C [10] . In the meantime, the tert ‐butoxyl radical abstracts a hydrogen atom from sulfonyl hydrazide 2 a , which initiates the generation of sulfonyl radicals ( D ) and the release of molecular nitrogen [5f,9d,11] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the hydrogen atom at the α‐carbon of substrate 1 a is abstracted by the tert ‐butoxyl radical to form α‐amino radical A . Then, the single‐electron oxidation of radical A by iodine provides iminium ion B , which is deprotonated to afford enamine C [10] . In the meantime, the tert ‐butoxyl radical abstracts a hydrogen atom from sulfonyl hydrazide 2 a , which initiates the generation of sulfonyl radicals ( D ) and the release of molecular nitrogen [5f,9d,11] .…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the hydrogen atom at the α-carbon of substrate 1 a is abstracted by the tert-butoxyl radical to form α-amino radical A. Then, the single-electron oxidation of radical A by iodine provides iminium ion B, which is deprotonated to afford enamine C. [10] In the meantime, the tert-butoxyl radical abstracts a hydrogen atom from sulfonyl hydrazide 2 a, which initiates the generation of sulfonyl radicals (D) and the release of molecular nitrogen. [5f,9d,11] Afterwards, the radical addition reaction of D and enamine C generates carbon radical E. Finally, radical E reacts with iodine to generate iodosulfone F, which undergoes HI elimination assisted by NaHCO 3 to afford the final product 3 a.…”
Section: Resultsmentioning
confidence: 99%
“…However, no conversion occurred when Et 3 N was replaced by metaldehyde and enamine ( 6 ) (Scheme c and d). These results strongly demonstrated that the imine intermediate from Et 3 N was preferentially captured by 3-aminoindazoles and prevented from converting to its enamine form under the NH 4 I-mediated aerobic oxidative conditions . Based on the blank experiments, it was confirmed that NH 4 I and molecular oxygen were indispensable for this transformation (Scheme e and f).…”
mentioning
confidence: 84%